2023
DOI: 10.1051/0004-6361/202346075
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the energetics of molecular superbubbles in PHANGS galaxies

Abstract: Context. Star formation and stellar feedback are interlinked processes that redistribute energy, turbulence, and material throughout galaxies. Because young and massive stars form in spatially clustered environments, they create pockets of expanding gas termed superbubbles, which retain information about the physical processes that drive them. As these processes play a critical role in shaping galaxy discs and regulating the baryon cycle, measuring the properties of superbubbles provides important input for ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 119 publications
1
7
0
Order By: Relevance
“…The stronger inhomogeneity in the inflow density/velocity induces stronger turbulence (e.g., the systematic survey by Kobayashi et al 2020), but the turbulent speed is expected to be on the order of the WNM sound speed (see Appendix C). Expansion of multiple supernova remnants also induces cloud compressions as often observed in galactic-scale numerical simulations (Girichidis et al 2016;Kim et al 2023a) and may explain the bubble features in nearby galaxies observed in JWST (Watkins et al 2023). Each compression event occurs at diverse angles at various times, and the generation of solenoidal mode turbulence locally occurs due to the deformed shock fronts.…”
Section: Applicability Of Converging Flow Results To the Ism In Realitymentioning
confidence: 68%
“…The stronger inhomogeneity in the inflow density/velocity induces stronger turbulence (e.g., the systematic survey by Kobayashi et al 2020), but the turbulent speed is expected to be on the order of the WNM sound speed (see Appendix C). Expansion of multiple supernova remnants also induces cloud compressions as often observed in galactic-scale numerical simulations (Girichidis et al 2016;Kim et al 2023a) and may explain the bubble features in nearby galaxies observed in JWST (Watkins et al 2023). Each compression event occurs at diverse angles at various times, and the generation of solenoidal mode turbulence locally occurs due to the deformed shock fronts.…”
Section: Applicability Of Converging Flow Results To the Ism In Realitymentioning
confidence: 68%
“…The CO velocity dispersion can be enhanced by low-velocity shocks originating from the interaction of molecular gas with late-time expansion of supernovae remnants (see Koo et al 2001;Zhou et al 2023), as well as from interaction with low-velocity shocks from H II region expansion driven by radiation pressure (Hill & Hollenbach 1978;Kothes & Kerton 2002;Watkins et al 2023). These low-velocity shocks are also predicted to enhance T e,[O III] .…”
Section: Temperatures Differences and Molecular Gas Propertiesmentioning
confidence: 99%
“…It has also been shown that shocks driven by the radiation pressure from H II region expansion, as well as supernova remnants, impact the surrounding cold molecular and ionized gas. If the velocity of the expansion is greater than the sound speed of the ionized gas, ∼10 km s −1 , a layer of shocked H gas will form in between the expanding ionization front and a surrounding molecular gas (Hill & Hollenbach 1978;Kothes & Kerton 2002;Tremblin et al 2014;Watkins et al 2023). The impact of shock interaction with molecular gas has been studied in 18 galaxies observed as part of PHANGS-ALMA (Leroy et al 2021a(Leroy et al , 2021b, where Watkins et al (2023) identified hundreds of superbubbles (i.e., pockets of expanding gas arising as byproducts of feedback).…”
Section: T E[n Ii] and T E[s Iii] As Accurate Tracers Of H II Region ...mentioning
confidence: 99%
See 2 more Smart Citations